Residence Permit Violations as a Non-Traditional Security Threat: An Analysis of Immigration Enforcement Data in North Jakarta Immigration Office (2023–2025) - Naufal Fadhilah; Muhammad Syahroni Rofii; Lin Yola (International Journal of Social Sciences and Humanities, 2026)
The increasing intensity of international mobility has generated new challenges for immigration control, including the misuse of residence permits by foreign nationals. This study aims to analyze the misuse of residence permits by Chinese nationals within the jurisdiction of the Class I Immigration Office TPI North Jakarta and examine its implications for national resilience. The research employs a descriptive qualitative approach using document analysis of Immigration Administrative Action (Tindakan Administratif Keimigrasian/TAK) data from 2023 to 2025. The analysis was conducted through the categorization of violations, identification of violation patterns, and interpretation of findings using the perspectives of non-traditional security threats and securitization theory. The findings reveal that Chinese nationals constituted the largest group subjected to immigration administrative actions during the study period. The most prevalent violations involved the misuse of residence permits for economic activities and employment that were inconsistent with the purposes for which the permits had been granted. These findings indicate that residence permit misuse is not merely an administrative issue but also reflects vulnerabilities in migration governance that may affect the economic and social dimensions of national resilience. Therefore, strengthening risk-based immigration supervision and enhancing inter-agency coordination are essential strategies for addressing non-traditional threats arising from international mobility.